Low socioeconomic class is a risk factor for upper and lower gastrointestinal symptoms: a population based study in 15 000 Australian adults. Issue 1 (1st July 2001) - Bytzer, P; Howell, S; Leemon, M; Young, L J; Jones, M P; Talley, N J
Abstract : BACKGROUND: The association of social class with health has been extensively studied, yet relationships between social class and gastrointestinal symptoms remain almost unexplored. AIMS: To examine relationships between social class and gastrointestinal symptoms in a population sample. METHODS: The prevalence of 16 troublesome gastrointestinal symptoms was determined by a postal questionnaire sent to 15 000 subjects (response rate 60%) and compared with a validated composite measure of socioeconomic status (index of relative socioeconomic disadvantage). Comparisons across social class were explored for five symptom categories (oesophageal symptoms; upper dysmotility symptoms; bowel symptoms; diarrhoea; and constipation). Results are reported as age standardised rate ratios with the most advantaged social class as the reference category. RESULTS: There were clear trends for the prevalence rates of all gastrointestinal symptoms to increase with decreasing social class. These trends were particularly strong for the five symptom categories. Lower social class was associated with a significantly (p<0.0001) higher number of symptoms reported overall and with a higher proportion of individuals reporting 1–2 symptoms and more than five symptoms. In both sexes, the most pronounced effects for subjects in the lowest social class were found for constipation (males: rate ratio 1.83 (95% confidence intervals (CI) 1.16–2.51); females: rate ratio 1.68 (95% CI 1.31–2.04)) and upper dysmotility symptoms (males: rate ratio 1.45 (95% CI 1.02–1.88); females: rate ratio 1.35 (95% CI 1.07–1.63)). Oesophageal symptoms and diarrhoea were not associated with social class. CONCLUSIONS: Troublesome gastrointestinal symptoms are linked to socioeconomic status with more symptoms reported by subjects in low socioeconomic classes. Low socioeconomic class should be considered a risk factor for both upper and lower gastrointestinal symptoms.